Christmas at Frances Kamp home 329 Rolling Hills Avenue, San Mateo - Watkins, Howard K. (1977)
Front: Christine Watkins, Howard Watkins, Frances Kamp, Back: Meredith Graham, Greg Graham, Gail Graham, Jackie Hijman, Marty Hijman, Jerry Kamp, Virginia Graham, Dorothy Nielsen